CORRELATION BETWEEN STUDENTS’ BUSINESS ENGLISH VOCABULARY MASTERY AND THEIR READING COMPREHENSION (A STUDY AT BUSINESS ENGLISH COMMUNICATION STUDENTS) - Sri Nurah Muyassyarah; Seny Luhriyani; Asfah, Indrawaty (International Journal of Business English and Communication, 2023)
This study is the correlational research that aimed to know the correlation between business English vocabulary mastery and reading comprehension of business English communication students. Business English vocabulary mastery as independent variable and reading comprehension as dependent variable. The population in this study is the students of Business English Communication study program class 2019, 2020, and 2021. The sample consist of 60 students. In doing this research, the data was obtained by business English vocabulary and reading comprehension tests. The analysis’s final result shows a positive correlation between students’ business English vocabulary mastery and their reading comprehension. The result shows that the students’ average level of business English vocabulary mastery was 68.91, and got fair scores in the table of business English vocabulary mastery rate scores. Meanwhile, the students’ reading comprehension score was 59.41 and also got fair scores in the table of reading comprehension rate scores. The result of Pearson Product Moment analysis, the correlation score was 0.981. Based on the table of criteria, it can be inferred from the index correlation table that the level of correlation is between 0.90-1.00 and the r product moment was in the very high correlation category. According to the interpretation of the correlation, the value of 0.981 is higher than rtable (0.250) at the 5% significance table. It means that the alternative hypothesis (H1) is accepted. Based on the findings above, the researcher concluded that the students’ business English vocabulary mastery correlated to their reading comprehension.